SELEBGRAM POLITICIANS: VIRTUAL SELF AND POLITICAL SELF-REPRESENTATION IN THE INSTAGRAM ERA - Yuyun Azizah Surya; Ratna Sari Dewi; Henri Subiakto (Pena Cendekia Insani, 2025)
This study investigates how a politician constructs and presents her virtual self through social media, focusing on Ananda, the elected Deputy Mayor of Banjarmasin for the 2025–2030 term. Employing a qualitative interpretative approach and virtual ethnography, this research explores strategies of self-representation, impression management, and emotional resonance in digital political communication during the 2024 regional election campaign. The analysis is grounded in dramaturgical theory and the concept of the virtual self, while also accounting for the digital cultural context that shapes symbolic interactions between politicians and the public. The findings indicate that Ananda’s self-representation on Instagram is perceived as authentic, consistent, and emotionally resonant with the digital public. The effectiveness of this strategy lies not only in an engaging and communicative online performance, but also in the alignment between her digital persona and offline presence. However, the study also affirms that political legitimacy continues to rely on structural factors such as political track record and party support. Consequently, social media is understood as a complementary arena that strengthens the affective bridge between politicians and society within the contemporary local political ecosystem.